Evolution and Development of the Inner Ear Efferent System: Transforming a Motor Neuron Population to Connect to the Most Unusual Motor Protein via Ancient Nicotinic Receptors - Fritzsch, Bernd; Elliott, Karen L. (Frontiers in Cellular Neuroscience, 2017)
All craniate chordates have inner ears with hair cells that receive input from the brain by cholinergic centrifugal fibers, the so-called inner ear efferents (IEEs). Comparative data suggest that IEEs derive from facial branchial motor (FBM) neurons that project to the inner ear instead of facial muscles. Developmental data showed that IEEs develop adjacent to FBMs and segregation from IEEs might depend on few transcription factors uniquely associated with IEEs. Like other cholinergic terminals in the peripheral nervous system, efferent terminals signal on hair cells through nicotinic acetylcholine channels, likely composed out of alpha 9 and alpha 10 units (Chrna9, Chrna10). Consistent with the evolutionary ancestry of IEEs is the even more conserved ancestry of Chrna9 and 10. The evolutionary appearance of IEEs may reflect access of FBMs to a novel target, possibly related to displacement or loss of mesoderm-derived muscle fibers by the ectoderm-derived ear vesicle. Experimental transplantations mimicking this possible aspect of ear evolution showed that different motor neurons of the spinal cord or brainstem form cholinergic synapses on hair cells when ears replace somites or eyes. Transplantation provides experimental evidence in support of the evolutionary switch of facial branchial motor neurons to become IEEs. Mammals uniquely evolved a prestin related motor system to cause shape changes in outer hair cells regulated by the IEEs. In summary, an ancient motor neuron population drives in craniates via signaling through highly conserved Chrna receptors a uniquely derived cellular contractility system that is essential for hearing in mammals.